ZnO nanoparticles act as supportive therapy in DSS-induced ulcerative colitis in mice by maintaining gut homeostasis and activating Nrf2 signaling - Li, Jinquan; Chen, Hanqing; Wang, Bing; Cai, Chengxu; Yang, Xu; Chai, Zhifang; Feng, Weiyue (Scientific reports, 2017)
Inflammatory bowel diseases (IBD) are widespread inflammatory diseases that cause debilitating health problems including cancer. In this study, we show that ZnO nanoparticle (ZnONP) treatment has markedly dose-dependent effects on the remission of dextran sulfate sodium (DSS)-induced ulcerative colitis in mice. We demonstrate the mechanism involves the antioxidant and anti-inflammatory abilities of ZnONPs to suppress ROS and malondialdehyde (MDA) production; increase GSH level; suppress proinflammatory cytokines IL-1β and TNF-α and myeloperoxidase (MPO). The ZnONP treatment is able to activate the Nrf2 pathway in the cellular antioxidant defense system. The novel finding is that ZnONP combined with mesalazine (5-ASA) can enhance the therapeutic efficacy of 5-ASA in the treatment of DSS-induced colitis. Lastly, we found that ZnONP treatment can restore the changes in special colonic bacteria of DSS-mice while the drug 5-ASA cannot. These results indicate that ZnONPs can act as a medical additive for the therapy of IBD.